Geomorphic Evolution and Changes of River Bends and Meanders in the Tributary of the Great Zab River Between the Iraqi-Turkish Borders and the Dereluk Dam (Iraqi National Journal of Earth Science (INJES), 2026)
This study addresses the changes and geomorphological evolution of the bends and meanders of the Greater Zab River in the study area situated in Dohuk Governorate, extending between the Iraqi-Turkish border and the Dereluk Dam. The focus of the study is on analyzing the changes in bends and meanders of the river over a period extending from 1990 to 2020. Geographic Information System technique and data from the Global Mapper program are employed. The study demonstrates varying morphometric changes and developments along the river font. Climatic elements played an important role in altering the landscape. The fluctuation of rainfall from one year to another affected water levels and discharge rates, as well as river erosion processes in the course of the Great Zab tributary and the activity of erosion on riverbanks. Furthermore, the variation in temperature negatively influences the tributary, particularly through evaporation. All these factors have contributed in landforms changes.
Keywords: Geomorphic Evolution, River Bends, Great Zab River, Dereluk Dam.